Keeping an Eye on Bisphosphonate Therapy in Myeloma: A Case Report of Ocular Inflammation Postzoledronic Acid Infusion - Rehman Faryal; Amjad Hayat (Case Reports in Hematology)
Bisphosphonates have evolved over the past decades from oral to more potent intravenous preparations. Along with significant paradigm shift in the management of myeloma over the past years, stronger nitrogen-containing bisphosphonates, due to their antiresorptive action on the bones, have found their way as a key and integral part in the management of bone disease in myeloma. Multiple randomized controlled trials have established efficacy of bisphosphonates in reducing skeletal-related events in myeloma. Some well-documented adverse events include acute-phase reactions, esophageal irritation, and osteonecrosis of the jaw. Across all clinical indications, the incidence of inflammatory eye reactions after bisphosphonate infusion ranges from 0.046% to 1%. However, data from myeloma patients are extrapolated from few reported cases in literature with varying management strategies including discontinuation, switching to different forms, and rechallenging with steroid cover. Inflammatory eye reactions can vary from self-limiting conjunctivitis and episcleritis to serious uveitis and vision-threatening orbital inflammation. We present a similar case of a patient with IgG kappa myeloma who developed flu-like symptoms followed by severe orbital inflammation within 48–72 hours after receiving zoledronic acid infusion. The patient was successfully managed with intravenous methyl prednisolone followed by oral tapering dose of steroids and discontinuation of further bisphosphonate therapy. A complete recovery was noted in a week’s time.